Excelsior Magnetic Bumper Co.: produce & install magnetic bumper / Mohd Saiful Azmeer Mohd Sazali [et al.] - Mohd Sazali, Mohd Saiful Azmeer; Ali, Muhammad khairi; Ibrahim, Siti Nursyafiqah Sazwa; Zahiruddin, Khairunisa Najwa; Mohd Fathil, Fatin Maisarah (2016)
This business plan is a guide and a roadmap for our business that outline goals and details how our plan to achieve those goals. This business plan contains of our administration, operation, marketing and financial plan that will help us in managing our business which is Excelsior Magnetic Bumper Co